Associations of financial inclusion with physical activity participation in later life. Issue 7 (July 2022) - Gyasi, Razak M.; Frimpong, Siaw; Lamptey, Richard Bruce; Amoako, Gilbert Kwabena; Asiki, Gershim; Adam, Anokye M.
Abstract: Background: Physical activity (PA) is a vital modifiable psychosocial intervention for promoting healthy longevity but problematically decreases with age. Innovative community-based strategies are recommended by the World Health Organization (WHO) to improve PA but prior research has seldom considered the interactive effect of financial inclusion, social networks, and sex differences on PA. In this study, we examine the role of sex differences and resourceful social networks in relation to the association of financial inclusion with PA among older Ghanaian people. Methods: The sample included 1201 adults aged ≥50 years who participated in the 2016-17 AgeHeaPsyWel-HeaSeeB study. We assessed financial inclusion with an eight-item Financial Instrument Questionnaire Scale and PA with the International Physical Activity Questionnaire Short Form (IPAQ-SF). Linear regressions and moderation analysis were used to test the hypothesized associations. Results: The mean financial inclusion and PA scores were 1.9(±1.8) and 9.0(±4.4) respectively. After full adjustment for potential confounders, a unit increase in financial inclusion was significantly and positively associated with increases in PA participation ( β = .308, p < .005) and also notable among those aged ≥65 years ( β = .413, p = .023). Crucially, the positive association between financial inclusion and PA was significantly modified by social networks ( β = .151, p < .001). However, the role of sex in this association was not robust. Conclusions: Findings emphasize the effect of financial inclusion on PA in old age, particularly when considering social networks. Programs to improve financial inclusion and social integration may benefit the acceptance and participation of PA among older adults. Abstract : Healthy longevity; Financial inclusion; Older people; Physical activity; Social networks; Ghana.